Faktor-Faktor Yang Berhubungan dengan Perilaku Deteksi Dini Kanker Payudara pada Wanita Pasangan Usia Subur di Desa Dawung Kebakkramat Karanganyar - Sari, Tutyan Mia; , Yuli Kusumawati, SKM., M. Kes (Epid); , Artika Fristi Firnawati, SKM (2013)
Secondary prevention with screening/early detection regarded as the most rational effort to reduce the number of deaths from breast cancer. The purpose of this study was to determine the factors associated with early detection measures of breast cancer in women in the village of Eligible Couple Dawung Kebakkramat Karanganyar. Methods This study uses observational design with cross - sectional approach. The population in this study were all women of childbearing age couples aged 20-50 years who live in the village Dawung, District Kebakkramat , Karanganyar totaling 113 people. The selection of the sample with simple random sampling with a sample size of 88 people. Test using the chi - square statistics using software. The results showed no significant relationship between knowledge and attitude to the behavior of early detection of breast cancer in women of childbearing age couples while not significantly associated ie between levels of education and employment to the behavior of early detection of breast cancer in women of reproductive age couples in the village Dawung, Kebakkramat Karanganya.